Seroepidemiology of Helicobacter pylori infection and hepatitis A in a rural area: evidence against a common mode of transmission. Issue 2 (1st August 1997) - Luzza, F; Imeneo, M; Maletta, M; Paluccio, G; Giancotti, A; Perticone, F; Focà, A; Pallone, F
Abstract : Background and aims —Recent studies have shown that the age-specific seroprevalence of H pylori infection parallels hepatitis A (HAV), suggesting similar modes of transmission. The aim of this study was to investigate the seroepidemiology of H pylori and HAV in the same setting. Patients —A sample of 705 resident subjects (273 men, age range 1–87 years, median 50) who attended the outpatient medical centre of the rural town of Cirò, Southern Italy (11 000 inhabitants) for blood testing were recruited. Methods —All subjects completed a structured questionnaire. A serum sample was drawn from each subject and assayed for H pylori IgG by a validated in house enzyme linked immunosorbent assay. Antibodies to HAV were determined in 466 subjects (163 men, age range 1–87 years, median 49). A measure of agreement between H pylori and HAV seropositivity, the κ statistic, was used. Results —Overall, 446 (63%) subjects were seropositive for H pylori . Of the 466 subjects screened for both H pylori and HAV, 291 (62%) were seropositive for H pylori and 407 (87%) for HAV. Cross-tabulation of these data showed that 275 (59%) were seropositive and 43 (9%) seronegative for both H pylori and HAV, 16 (3%) were seropositive for H pylori, and 132 (28%) were seropositive for HAV (OR = 5.6, CI 3 to 10). There was a parallel, weakly correlated ( r = 0.287) rise in the seroprevalence of the two infections with increasing age. However, the agreement between H pylori and HAV seropositivity was little better than chance (κ = 0.21) and in those aged less than 20 years it was worse than chance (κ = –0.064). Furthermore, multiple logistic regression analysis did not show any risk factor shared by both infections. Conclusions —The correlation between H pylori and HAV reflects the age-specific seroprevalence of both infections rather than a true association . This study provides evidence against a common mode of transmission of H pylori and HAV.